Optical Guided-wave Chemical and Biosensors II - Zourob, Mohammed; Lakhtakia, Akhlesh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
For the first time, distinguished scientists from key institutions worldwide provide a comprehensive approach to optical sensing techniques employing the phenomenon of guided wave propagation for chemical and biosensors. This includes both state-of the-art fundamentals and innovative applications of these techniques. The authors present a deep analysis of their particular subjects in a way to address the needs of novice researchers such as graduate students and post-doctoral scholars as well as of established researchers seeking new avenues. Researchers and practitioners who need a solid foundation or reference will find this work invaluable. This second of two volumes covers the incorporation of periodic structures in waveguides to exploit the Bragg phenomenon, optical fiber sensors, hollow waveguides and micro-resonators as well as a review of the tremendous expansion of terahertz technology for sensing applications.
Waveguide Sensors with Periodic Structures -- Nano-structured Silicon Optical Sensors -- Resonant Waveguide Grating Biosensor for Microarrays -- Resonant Biochemical Sensors Based on Photonic Bandgap Waveguides and Fibers -- Nanophotonic and Subwavelength Structures for Sensing and Biosensing -- Optical-Fiber Sensors -- Fiber-Optic Chemical and Biosensors -- Applications of Fiber Gratings in Chemical and Biochemical Sensing -- Hollow-Optical Fiber Probes for Biomedical Spectroscopy -- Hollow-Waveguide and Micro-Resonator Sensors -- Liquid-Core Waveguide Sensors -- Capillary Waveguide Biosensor Platform -- Label-Free Optical Ring Resonator Bio/Chemical Sensors -- Terahertz Biosensing -- Terahertz-Biosensing Technology: Progress, Limitations, and Future Outlook -- Erratum.
Keywords: Chemistry; Analytical biochemistry; Chemical engineering; Biochemistry; Chemistry; Analytical Chemistry; Industrial Chemistry/Chemical Engineering; Medical Biochemistry; Optics, Optoelectronics, Plasmonics and Optical Devices